Opportunities to Respond for Students With Emotional and Behavioral Disorders in Inclusive Classrooms. (March 2022) - Whitney, Todd; Ackerman, Kera B.; Cooper, Justin T.; Scott, Terrance M.
Students who are actively engaged in learning have a higher probability of academic and behavioral success in the classroom. One effective teaching practice that increases student engagement is providing students with frequent opportunities to respond (OTR). This article provides practitioners with a range of OTR strategies that include verbal, non-verbal, and partner responses. In addition, recommendations are provided on how these strategies can be effectively implemented in inclusive classrooms to increase engagement of students with school-based behavior problems, including those with and at risk for emotional and behavioral disorders.